1014. Factors Associated with Switching from Tenofovir Diproxil Phosphate to a Tenofovir Alafenamide Based Regimen in a Cohort with Unrestricted Access to Care and Medications. (31st December 2020) - Ganesan, Anuradha; Won, SeungHyun; Ewers, Evan C; Bradley, William; Schofield, Christina; Utz, Gregory; Colombo, Rhonda; Blaylock, Jason M; Lalani, Tahaniyat; Kronmann, Karl; Okulicz, Jason; Maves, Ryan C; et al.
Abstract: Background: Background - Tenofovir alafenamide (TAF) is associated with fewer renal and bone toxicities than tenofovir disoproxil phosphate (TDF). Hence, most experts suggest switching to TAF. We examined factors associated with switching to TAF in the US Military HIV Natural History Study (NHS), a cohort of people living with HIV who have unrestricted access to care and medications. Methods: Methods - The first formulation of TAF received FDA approval on 1 November 2015; hence, we included all NHS participants with visits between November 2015 and March 2019. Patient factors including race, gender, CD4 count, antiretroviral therapies (ART), viral load, HIV diagnosis era, presence of comorbidities (cancer, heart disease, dyslipidemia, kidney disease and obesity), were assessed for association with a switch to TAF with a logistic regression model. Results: Results - Of the 1678 eligible participants, 1324 (63%) had received a TDF-based regimen. Participants who received a TDF-regimen were 94% male 44% African-American [AA], 39% Caucasians and 17% Hispanic. About half the participants who received TDF-based ART switched to a TAF-based regimen (n=682, 52%). Of the 425 (32%) participants receiving TDF/FTC co-formulated with efavirenz, 48% (n=206) switched to TAF. The proportions switching to TAF were higher in those receiving TDF/FTC co-formulated with rilpivirine [59%, n=90] or elvitegravir/cobicistat [68%, n=146]. The common ART regimens after the switch were: TAF co-formulated with elvitegravir/cobicistat (46%), rilpivirine (16%) or bictegravir (12%) and TAF/FTC combined with dolutegravir (15%). In an adjusted analysis, older participants, and participants receiving TDF/FTC in combination with efavirenz, dolutegravir, raltegravir, boosted protease inhibitors or a combination of boosted protease inhibitors and integrase inhibitors (other) were less likely to switch, table 1. Conclusion: Conclusions - Despite the unrestricted access to care and ART in the NHS, only half of the participants switched to TAF. Participants on efavirenz-containing regimens were less likely to switch to a TAF-based regimen, possibly due to the lack of a co-formulated single tablet. These trends need to be followed and barriers to switching to TAF (both patient and provider) need examination. Table 1- Factors associated with switching to a Tenofovir Alafenamide Based Regimen Disclosures: All Authors : No reported disclosures